(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
Legal culture is also an integral part of the general culture of our people. In the minds of people, there should be such confidence in legal culture that any person who has legal knowledge and can apply it in practice should be considered cultured and educated. Currently, there is talk of creating a comprehensive and regular system of forming legal culture so that the lowest layer of our society can have a high level of legal awareness and be able to apply their legal knowledge in everyday life.